Implementing gender quotas in academia: a practice lens. Issue 4 (20th May 2019) - Voorspoels, Jolien; Bleijenbergh, Inge
Abstract : Purpose: The purpose of this paper is to explore the practices utilized by university actors when implementing gender quotas, and study how these practices affect gender equality in academic decision-making bodies. Design/methodology/approach: The study applies a practice theory lens to the case study of a Belgian university implementing a gender quota by performing 26 semi-structured interviews with actors, and collecting and analyzing relevant organizational documents. Findings: This study shows that university actors implement gender quotas through three practices: gender-specific calls, scouting and "playing around". Identifying this variation in practices helps to understand both actors' sense-making of compliance with gender quotas and women's decision-making power in academic bodies. Research limitations/implications: This study explores how practices interact with the organization's broader context and its power dynamics. In future studies, adding ethnographic observations would strengthen the practice approach. Practical implications: The study indicates that implementing gender quotas can foster women's representation in decision-making, but that a strictly procedural sense-making of gender quotas could also undermine this. Universities should continue implementing gender quotas, further analyze their implementation practices and comprehensively adapt their organizational policies and practices to comply with gender equality goals substantively. Originality/value: Through a practice theory approach, this paper offers original insight into how actors comply with gender quotas. Uncovering the implementation process in particular, the paper reveals how gender quotas could foster gender equality in academic decision-making.